Integrin Beta 5 Is a Prognostic Biomarker and Potential Therapeutic Target in Glioblastoma - Zhang, Lu-yang; Guo, Qing; Guan, Ge-fei; Cheng, Wen; Cheng, Peng; Wu, An-hua (Frontiers in Oncology, 2019)
Abstract Background: Glioblastoma (GBM) is the most lethal cancer of the central nervous system. Integrin beta 5 (ITGB5) is thought to be involved in intercellular signal transduction and regulation of tumor initiation and progression. However, the function of ITGB5 in GBM is not known. Methods: To address this question, we evaluated the expression level of ITGB5 in clinical specimens by immunohistochemistry and western blotting, as well as the association between ITGB5 expression and GBM patient survival using data from Chinese Glioma Genome Atlas and The Cancer Genome Atlas. The biological function of ITGB5 in GBM was investigated by Gene Ontology, gene set enrichment. and in vitro loss-of-function experiments using glioma cells. Results: Among integrin family members, ITGB5 showed the greatest difference in expression between low-grade glioma and GBM. Elevated ITGB5 expression was highly correlated with glioma progression and a mesenchymal subtype and poor survival in GBM patients. ITGB5 was found to be associated with regulation of the immune response and angiogenesis in GBM, and was required for migration and invasion of glioma cells and tube formation by endothelial cells. Conclusions: These data indicate that ITGB5 can serve as a predictive biomarker for GBM patient survival and is a potential therapeutic target in GBM treatment.